The role of implicit measures of motivation in health, relationships, and well-being - Keatley, D.; Hagger, Martin; Heym, N. (Routledge, 2013)
Research into motivation underpinning health and well-being has traditionally adopted explicit, self-report questionnaires. Recently, there has been growing support for the role of implicitly measured motivation on health, relationships, and well-being. Dual-systems models have been proposed to account for the roles of both explicit/reflective and implicit/impulsive processes on a range of behaviours. This presentation will outline a program of research (N = 70 to 162) that shows the role of implicit and explicit motivation on health behaviours, relationships, and wellbeing. Across several studies, dual-systems models were tested, and the unique contribution of implicit measures of motivation assessed. Analyses indicate that implicit motivation offers additive prediction of a range of health behaviours and relationship factors; however, consideration of the outcomes shows that implicit motivation may better predict spontaneous or unplanned behaviours. This provides support for some of the patterns of interaction hypothesised in dual-systems models. Future research and implications are also outlined.